Pengaruh Dosis Pupuk NPK Phonska dan Pupuk Hayati Petrobio Terhadap Pertumbuhan dan Hasil Tanaman Kacang Panjang (Vigna sinensis L.) - Aini, Zuliatul; Nikmatullah, Aluh; Suryaningsih, Liana (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
The aim of this study was to determine the effect of NPK Phonska dosage and Petrobio biofertilizer on growth and yield of long bean plants. The research was conducted from January to April 2024 at Kelayu Utara, Selong District, East Lombok. The experiment was designed according to a factorial Randomized Block Design (RBD) design with 2 factors: NPK Phonska fertilizer at five levels and Petrobio biofertilizer at two levels, thus there were 10 treatment combinations, which were 3 times. The data were analyzed using ANOVA at the 5% level, then further tested using an Significant Difference (LSD) test of 5% significance level. The results showed a significant interaction between NPK Phonska fertilizer dosage and Petrobio biofertilizer in influencing plant height at 35 days after planting (DAP) and the number of leaves at 21 DAP. NPK Phonska fertilizer, as a single factor, significantly affected plant height at 21 and 28 DAP, the number of leaves at 21, 28, and 35 DAP, flowering time, the number of flowers, the percentage of flowers turning into pods, pod weight, pod length, and pod diameter. Petrobio biofertilizer, as a single factor, significantly affected plant height at 21 DAP, the number of leaves at 28 DAP, and flowering time. In this study, the best NPK Phonska fertilizer dosage for growth and yield of long bean Â plants was 16 g/plant.